Three little boys and two women - Martin & Rita Rowe (photographic studio):::Creator::::::::::::
Photograph shows two women and three little boys. The woman on the right is dressed in a top and skirt made of shiney material and elaborately embroidered. The woman on the left and the three boys are admiring the outfit.